Faktor-faktor yang melakukan tindakan Transfer Pricing pada Perusahan Sub Sektor Pertambagnan di Bursa Efek Indonesia - Sukma , Suci Asral (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
One of the methods of tax avoidance used by big business is transfer pricing. In management accounting, "transfer pricing" is a policy applied by a company when delivering goods or services between departments, between affiliated companies, or between subsidiaries in order to measure its performance. This study aims to re-examine the effect of the exchange rate, company size, and foreign ownership on transfer pricing in mining subsector companies. The research method required for this research is quantitative. This study's population is Mining Subsector Companies that are Electricity on the Indonesia Stock Exchange from 2016 to 2019. The data collection technique in this study is in the form of financial report documents. The sample in this study was determined by the purposive sampling method, with a total sample size of 36. The data analysis technique used was descriptive statistics using the SPSS Econometric Views application. testing the data using the Chow Test, Hausman Test, Normality Test, Heteroscodesticity Test, Multicollinearity Test, Autocorrelation Test, and Panel Data. The results of this study are yes, the exchange rate has no effect on Transfer Pricing, while foreign ownership and company size have an effect on Transfer Pricing.